People and Planet: Values, Motivations and Formative Influences of Individuals Acting to Mitigate Climate Change. (1st April 2017) - Howell, Rachel; Allen, Simon
Abstract : This paper presents results from a survey of 344 individuals who engage in climate change mitigation action, contributing to debates about whether it is necessary to promote 'nature experiences' and biospheric values to encourage pro-environmental behaviour. We investigate three factors - values, motivations and formative experiences - that underlie such behaviour, but that usually have been considered in isolation from each other. In contrast to previous studies of environmentalists' significant life experiences, outdoor/nature experiences were not frequently mentioned as being influential. Altruistic concerns about climate change impacts on future human generations and on poorer or more vulnerable people were considered more motivating than other reasons for action. There was no significant difference in how respondents rated altruistic and biospheric values. Variations in responses from those involved in 'biospherically-oriented' organisations (such as traditional environmental or conservation organisations) versus those involved in climate change groups suggest that there are different routes into climate change mitigation action, and our results show that it is not essential to cultivate biospheric values or the love of nature to encourage such action.